The politics of Islamic law local elites, colonial authority, and the making of the Muslim state - Hussin, Iza R. (The University of Chicago Press, 2016)
In [this book], Iza R. Hussin compares India, Malaya, and Egypt during the British colonial period in order to trace the making and transformation of the contemporary category of "Islamic law." She demonstrates that not only is Islamic law not the shariu06E5a, but that its present institutional forms, substantive content, symbolic vocabulary, and relationship to state and society - in short, its politics - are built upon foundations laid during the colonial encounter.